An efficient and high-throughput method for the evaluation of mitochondrial dysfunction in frozen brain samples after traumatic brain injury - Vekaria, Hemendra J.; Kalimon, Olivia J.; Prajapati, Paresh; Velmurugan, Gopal V.; Sullivan, Patrick G. (Frontiers in Molecular Biosciences, 2024)
Mitochondrial function analysis is a well-established method used in preclinical and clinical investigations to assess pathophysiological changes in various disease states, including Traumatic Brain Injury (TBI). While there are multiple approaches to assess mitochondrial function, one common method involves respirometric assays utilizing either Clark-type oxygen electrodes or fluorescent-based Seahorse analysis (Agilent). However, these functional analysis methods are typically limited to the availability of freshly isolated tissue samples due to the compromise of the Electron Transport Chain (ETC) upon storage, caused by freeze-thaw mediated breakdown of mitochondrial membranes. In this study, we propose and refine a method for evaluating electron flux through the ETC, encompassing Complex I, II, and IV, in frozen homogenates or mitochondrial samples within a single well of a Seahorse plate. Initially, we demonstrate the impact of TBI on freshly isolated mitochondria using the conventional Oxidative Phosphorylation Protocol (OxPP), followed by a comparison with ETC analysis conducted on frozen tissue samples within the context of a controlled cortical impact (CCI) model of TBI. Additionally, we explore the effects of mitochondrial isolation from fresh versus snap-frozen brain tissues and their storage at -80°C, assessing its impact on ETCP activity. Our findings indicate that while both sets of samples were frozen at a single time point, mitochondria from snap-frozen tissues exhibited reduced injury effects compared to preparations from fresh tissues, which were either homogenized or isolated into mitochondria and subsequently frozen for later use. Thus, we demonstrate that the preparation of homogenates or isolated mitochondria can serve as an appropriate method for storing brain samples, allowing for later analysis of mitochondrial function following TBI using ETCP.